Fastighetsföretagens väg mot klimatneutralitet - Ahmad,Jasmin (0349-4969, 2025)
The ongoing climate change is not only a challenge for the environment but also for economic and social development. The continuing rise of consumption and production of natural resources that needs to be preserved is affecting the environment. The urbanization is contributing to a higher demand of commercial buildings and housing, this needs resources like building material which releases carbon dioxide emissions. The human impact on earth has created an environmental impact and a lot of the impact comes from the construction- and real estate sector. Large proportion of energy use and waste is linked to this sector. To minimize the environmental impact from organizations that contribute to emissions there are national and international goals that work like a driving force to help the companies reduce the negative impact they have on the climate. The purpose of this work is to look into what real estate companies do to reach these goals. The questions this thesis is focusing on are: - How do real estate companies work until 2045 to reach the net zero carbon emissions goal? - What do real estate companies do to contribute to the sustainability goals, affordable and clean energy, sustainable cities and communities and responsible consumption and production? - Are the real estate companies going to reach Sweden's milestone target 2045? - Are real estate companies looking at the EU-taxonomy? - What are the problems a real estate company comes across while working to become climate neutral? In this study qualitative studies have been used. To get a background about the research area a literature survey was made and the results are based on interview studies and document studies. To contribute to the sustainable development goal, affordable and clean energy the real estate companies are working with energy efficiency, installing solar cells and are buying fossil free energy. By localizing close to public transportation and planning bicycle paths to their properties and making green transportation an option for employees and tenants. Many of the companies work with creating safe and secure neighborhoods by having different operations on the estates. It is not always possible to create green areas in cities but they try to convert hard ground to green surface and make an effort to favor biodiversity. These factors contribute to sustainable cities and communities. To be able to consume sustainably the production needs to be sustainable. With circularity, companies try to choose materials and products that are reusable and non-toxic. Because a huge amount of emissions comes from projects and scope 3 it is important to choose the right materials from the start, materials that have low emissions and that can be reused. Most of the real estate companies believe that they can reach the 2045 climate goal. They are able to minimize their direct emissions, it is the indirect emissions that are difficult to reduce because they are not able to control the supply on the market. Most of the companies do not need to report according to the EU-taxonomy but many still choose to do so. They mostly try to reach climate goal 1, climate change mitigation.
Keywords: Klimatpåverkan; miljömål; hållbar utveckling; globala målen